Global status of recycling waste solar panels: A review. (May 2018) - Xu, Yan; Li, Jinhui; Tan, Quanyin; Peters, Anesia Lauren; Yang, Congren
Highlights: Solar panel recycling minimizes waste of environmental and economic resources. Several processing methods from the literature are evaluated. The status of the management for waste solar panels are systemically reviewed and discussed. Policy should be formulated to encourage recycling of waste solar panels. Manufacturers should take greater responsibility for recycling. Abstract: With the enormous growth in the development and utilization of solar-energy resources, the proliferation of waste solar panels has become problematic. While current research into solar panels has focused on how to improve the efficiency of the production capacity, the dismantling and recycling of end-of-life (EOL) panels are seldom considered, as can be seen, for instance, in the lack of dedicated solar-panel recycling plants. EOL solar-panel recycling can effectively save natural resources and reduce the cost of production. To address the environmental conservation and resource recycling issues posed by the huge amount of waste solar panels regarding environmental conservation and resource recycling, the status of the management and recycling technologies for waste solar panels are systemically reviewed and discussed in this article. This review can provide a quantitative basis to support the recycling of PV panels, and suggests future directions for public policy makers. At present, from the technical aspect, the research on solar panel recovery is facing many problems, and we need to further develop an economically feasible and non-toxic technology. The research on solar photovoltaic panels' management at the end of life is just beginning in many countries, and there is a need for further improvement and expansion of producer responsibility.